Performance and Feasibility Analysis of a Micro-Enterprise Laundry Business - Abdur Rahman Sutarmo; Sutrisno Sutrisno; Riyo Riyadi; Ruspian Ruspian (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study analyzes the performance and financial feasibility of a micro-enterprise laundry business operating in the service sector. Using a descriptive quantitative approach, primary data were collected through structured interviews with the business owner and employees to capture detailed information on operational and financial conditions. Financial performance was evaluated by analyzing revenue, operating costs, net income, and the Benefit Cost ratio as an indicator of business feasibility. The results indicate that the laundry enterprise achieved an average Benefit Cost ratio of 2.02 during the observation period, demonstrating strong financial feasibility and efficient resource utilization. This finding suggests that the business is capable of generating returns that significantly exceed its operational costs. Furthermore, the analysis reveals that effective cost control, accurate financial recordkeeping, and stable service demand play a crucial role in sustaining profitability. The study highlights that micro-enterprise laundry businesses have considerable potential for long-term sustainability when supported by sound financial management practices. Strengthening systematic cost monitoring, improving financial planning, and maintaining service quality are recommended to enhance operational efficiency and ensure continuous business growth. The findings provide practical insights for micro-entrepreneurs and policymakers seeking to support the development and resilience of small-scale service businesses.